Development of a security system organization model taking into account the impact of the external environment - Dzheniuk, Nataliia; Zaika, Viktor; Yevseiev, Serhii; Tarasenko, Yevhen; Moskalenko, Artem; Kryvosheiev, Vitalii; Kravchenko, Serhii; Holdobin, Serhii; Ismahilov, Artur; Syvachenko, Ihor (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of ensuring the security of cyber-physical systems under the influence of external destructive factors, in particular information, radio-electronic, and physical attacks aimed at disrupting continuous system operation. The paper addresses the problem of determining the optimal structure of an airborne mobile network within a cyber-physical system, specifically the ratio between operational and protective elements that ensures maximum system stability under targeted attacks. The presented modeling results are based on a minimax formulation of the interaction between the system and the external environment, which makes it possible to determine critical threshold values of stability parameters. The applied mathematical model describes both the optimal strategy of the attacking environment and the optimal initial structure of the system itself. This enables the identification of relationships between the initial ratio of operational and protective components and the minimum adversary resources required for complete system destruction. It is shown that an optimal configuration of protective elements forces the attacking environment to expend 1.5–2 times more resources compared to suboptimal structures. A correctly selected ratio of system elements slows down the degradation of the protective contour. The developed mathematical model confirms the existence of an optimal strategy for external environment behavior and an optimal initial structure of the airborne mobile network of the cyber-physical system. This approach improves the design process of cyber-physical systems at early stages, enhances their survivability, and contributes to the development of a methodology for integrated protection of airborne mobile networks under challenging real-world conditions